Studi Literatur: Eksplorasi Inovasi Produk UMKM dan Peran Manajemen Sumber Daya Manusia Dalam Meningkatkan Kepuasan Pelanggan - Chandra Sagul Haratua; Warti, Warti; Kendi Widiantari; Siti Nuraeni; Puput Nia Nuroniah (FKIP, Universitas Palangka Raya, 2024)
This study aims to explore product innovation in MSMEs and the role of human resource management (HRM) in enhancing customer satisfaction. Using a literature review approach, this research collects and analyzes various relevant sources on product development and HRM in the context of MSMEs. Product innovation in MSMEs is considered a key factor in gaining a competitive edge in the market, involving market research, the application of modern technology, and sustainable product improvements. Additionally, effective HRM plays a critical role in enhancing employees' capabilities through competency-based training programs such as skill training, digital marketing, and inventory management. These training programs aim to improve employees' skills in facing dynamic market challenges and enhance customer service quality. The study also shows that a work culture supporting collaboration and creativity, as well as involving employees in strategic decision-making, contributes to product innovation and customer satisfaction. The results indicate that effective HRM can increase customer loyalty and competitive advantage for MSMEs, while continuous product innovation is crucial for achieving sustainable business growth